The costs of transgenerational immune priming for homologous and heterologous infections with different serotypes of dengue virus in Aedes aegypti mosquitoes - Cime-Castillo, Jorge; Vargas, Valeria; Hernández-Tablas, Juan Manuel; Quezada-Ruiz, Edgar; Díaz, Grecia; Lanz-Mendoza, Humberto (Frontiers in Immunology, 2023)
The immune system is a network of molecules, signaling pathways, transcription, and effector modulation that controls, mitigates, or eradicates agents that may affect the integrity of the host. In mosquitoes, the innate immune system is highly efficient at combating foreign organisms but has the capacity to tolerate vector-borne diseases. These implications lead to replication, dissemination, and ultimately the transmission of pathogenic organisms when feeding on a host. In recent years, it has been discovered that the innate immune response of mosquitoes can trigger an enhanced immunity response to the stimulus of a previously encountered pathogen. This phenomenon, called immune priming, is characterized by a molecular response that prevents the replication of viruses, parasites, or bacteria in the body. It has been documented that immune priming can be stimulated through homologous organisms or molecules, although it has also been documented that closely related pathogens can generate an enhanced immune response to a second stimulus with a related organism. However, the cost involved in this immune response has not been characterized through the transmission of the immunological experience from parents to offspring by transgenerational immune priming (TGIP) in mosquitoes. Here, we address the impact on the rates of oviposition, hatching, development, and immune response in Aedes aegypti mosquitoes, the mothers of which were stimulated with dengue virus serotypes 2 and/or 4, having found a cost of TGIP on the development time of the progeny of mothers with heterologous infections, with respect to mothers with homologous infections. Our results showed a significant effect on the sex ratio, with females being more abundant than males. We found a decrease in transcripts of the siRNA pathway in daughters of mothers who had been exposed to an immune challenge with DV. Our research demonstrates that there are costs and benefits associated with TGIP in Aedes aegypti mosquitoes exposed to DV. Specifically, priming results in a lower viral load in the offspring of mothers who have previously been infected with the virus. Although some results from tests of two dengue virus serotypes show similarities, such as the percentage of pupae emergence, there are differences in the percentage of adult emergence, indicating differences in TGIP costs even within the same virus with different serotypes. This finding has crucial implications in the context of dengue virus transmission in endemic areas where multiple serotypes circulate simultaneously.